The effect of using two types of cognitive strategies stimulants on scientific thinking among fourth grade students - Rahi, Qahtan Fadhil; Katoon, Duaa Raheem; Sabti, Yousif Mousa (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
This study highlights the need for modernizing teaching methods in response to the progress made in various scientific fields in the last quarter of the previous century. The focus is on developing teaching strategies that help students become independent and conscious citizens who think scientifically. The emphasis is on cognitive methods and means that teachers can use to activate cognitive strategies and urge students to use them in order to learn effectively. The abstract also underscores the importance of aligning educational goals with the latest scientific developments to prepare students for the challenges of the 21st century. It emphasizes the importance of developing cognitive methods and means for teachers to use in the classroom to activate cognitive strategies and help students learn in a scientific way. The goal is to produce independent and conscious citizens who can think critically and employ their knowledge effectively.